2014
DOI: 10.1101/gad.232470.113
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological rescue of Ras signaling, GluA1-dependent synaptic plasticity, and learning deficits in a fragile X model

Abstract: Fragile X syndrome, caused by the loss of Fmr1 gene function, is the most common form of inherited mental retardation, with no effective treatment. Using a tractable animal model, we investigated mechanisms of action of a few FDA-approved psychoactive drugs that modestly benefit the cognitive performance in fragile X patients. Here we report that compounds activating serotonin (5HT) subtype 2B receptors (5HT 2B -Rs) or dopamine (DA) subtype 1-like receptors (D 1 -Rs) and/or those inhibiting 5HT 2A -Rs or D 2 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 95 publications
(167 reference statements)
2
47
0
Order By: Relevance
“…The following strategies were confirmed in studies using Drosophila models of fragile X syndrome (FXS): metabotropic glutamate receptor (mGluR) [167], gamma-aminobutyric acid (GABA) [168] (but see [169]), lithium [167], minocycline [170], phosphodiesterase-4 (PDE-4) [ A recent study suggested that simultaneous stimulation of D1R and serotonin (5HT) receptors rescued impaired synaptic AMPA receptor insertion and plasticity, and improved fear conditioning and Y maze learning deficits [115]. § Simultaneous inhibition of mGlu5 and CB1R was additive in this study.…”
Section: Macro-orchidismmentioning
confidence: 97%
See 1 more Smart Citation
“…The following strategies were confirmed in studies using Drosophila models of fragile X syndrome (FXS): metabotropic glutamate receptor (mGluR) [167], gamma-aminobutyric acid (GABA) [168] (but see [169]), lithium [167], minocycline [170], phosphodiesterase-4 (PDE-4) [ A recent study suggested that simultaneous stimulation of D1R and serotonin (5HT) receptors rescued impaired synaptic AMPA receptor insertion and plasticity, and improved fear conditioning and Y maze learning deficits [115]. § Simultaneous inhibition of mGlu5 and CB1R was additive in this study.…”
Section: Macro-orchidismmentioning
confidence: 97%
“…In the case of FXS, increased density and immature appearance of dendritic spines were detected in patients and mouse models [171,193], and have been widely used to test therapeutic strategies. Pharmacologic and genetic modification of many molecular targets, including neurotransmitter receptors, [62] Lymphoblastoid cells [64], fibroblasts [66] AMPA receptor internalization Increased [43,62,114] N o Altered cellular signaling Increased [64,111,113] or decreased PI3K/mTOR phosphorylation [115]; increased ERK1/2 phosphorylation [112]; increased GSK3β phosphorylation [116] Lymphoblastoid cells [64], lymphocytes and brain tissue [65], fibroblasts [66] Cellular…”
Section: Synaptic Neuronal and Network Defects To Test Treatment Stmentioning
confidence: 99%
“…Organotypic hippocampal cultured slices were prepared from postnatal 6-to 7-d-old (P6-P7) male and female Sprague Dawley rats, wild-type mice, and Ca V 3.2 knockout (Orestes et al 2009) mice bred congenically on the C57BL/6 background, following our previous studies (Qin et al 2005;Lim et al 2014). All procedures for animal surgery and maintenance were performed following protocols approved by the animal care and use committee of the University of Virginia and in accordance with National Institutes of Health guidelines.…”
Section: Cultured and Acute Slice Preparationmentioning
confidence: 99%
“…Pre-embedding immunogold labeling was carried out following the procedures of previous studies (Erisir and Harris 2003;Kielland et al 2009). In brief, 1 µg/mL rabbit anti-GluA2/3 (Millipore, AB1506) was used to detect AMPA-Rs because of the nonrectified AMPA responses seen in CA1 and L5 pyramidal neurons (Zhu 2009;Lim et al 2014) and TRN neurons (values for rectification: R VB stim = 1.51 ± 0.06 and R cortex stim = 1.54 ± 0.08; n = 19 from nine animals), an indicator of incorporation of GluA2 subunits in the majority of AMPA-Rs. A mouse monoclonal anti-GluN1 (Luo et al 1997) was used to detect the obligatory GluN1 subunits of NMDA-Rs.…”
Section: Immunostaining and Immunoelectron Microscopymentioning
confidence: 99%
“…Cultured slices were prepared from postnatal 6-7-day-old male and female rats following previously reported procedure Myers et al 2012;Lim et al 2014). All procedures for animal surgery and maintenance were performed following protocols approved by the Animal Care & Use Committee of the University of Virginia (Protocol No.…”
Section: Biochemical Analysismentioning
confidence: 99%